A Grid-Connected Microgrid Optimal Allocation Method Considering Self-Balancing Rate. (October 2020) - Quanming, Zhang; Xiaodi, Zhang; Ke, Sun; Dan, Zhou; Wei, Tong
Abstract: Microgrid optimal allocation is the primary problem that needs to be solved in the stage of microgrid planning and design. Whether the optimal allocation scheme is reasonable or not will directly determine the safe operation and economic benefits of microgrid. Unreasonable allocation scheme will lead to higher power supply costs and poor performance, and can not even reflect the inherent superiority of microgrid. In this paper, based on some indicators such as the self-balancing rate, the power fluctuation rate of the tie line, and the proportion of spontaneous self-use, the effect of the different operation strategies of the wind/light/storage grid-type microgrid is analyzed firstly. Then, an optimal allocation method for grid-connected microgrid is proposed. Furthermore, based on the economic scheduling operation strategy, considering the initial investment cost, replacement cost, operation maintenance cost, residual value and purchase electricity cost, the optimal allocation scheme with different self-balancing rate is compared.